Designing Urban Intergenerational Co-Living Environments: Enhancing Community Engagement and Psychological Well-Being for the Elderly Through Sports and Recreation - Xin Cheng; Ying Yan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the context of an aging society, family-based elder care has become the preferred choice, with intergenerational co-living models, where elderly individuals reside with their children and grandchildren, posing higher demands on urban residential environments. This study analyzes the factors, needs, and challenges associated with urban intergenerational co-living within the framework of family-based elder care. It aims to propose design strategies that cater to the specific living requirements of elderly individuals at various stages of aging while accommodating the needs of other family members, including children and grandchildren. The study also addresses the complexities introduced by family planning policy reforms, which influence intergenerational co-living environments. Strategies are suggested to create inclusive, livable spaces that balance the needs of all generations, fostering stronger familial bonds and harmonious development of intergenerational relationships. From a sports psychology perspective, this research emphasizes the role of recreational and sports activities in intergenerational co-living environments. By incorporating shared spaces for physical activities, sports, and recreation, the proposed design strategies promote psychological well-being, enhance social engagement, and improve overall quality of life for all family members. These insights provide a foundation for integrating physical and emotional health into urban residential planning, contributing to sustainable and harmonious living environments.